Zero-dimensional to three-dimensional nanojoining: current status and potential applications. Issue 79 (10th August 2016) - Ma, Ying; Li, Hong; Bridges, Denzel; Peng, Peng; Lawrie, Benjamin; Feng, Zhili; Hu, Anming
Abstract : As devices have become smaller, nanomaterials have become the preferred manufacturing building blocks due to lower material and joining energy costs. This review surveys progress in nanojoining methods, as compared to conventional joining processes. Abstract : The continuing miniaturization of microelectronics is pushing advanced manufacturing into nanomanufacturing. Nanojoining is a bottom-up assembly technique that enables functional nanodevice fabrication with dissimilar nanoscopic building blocks and/or molecular components. Various conventional joining techniques have been modified and re-invented for joining nanomaterials. This review surveys recent progress in nanojoining methods, as compared to conventional joining processes. Examples of nanojoining are given and classified by the dimensionality of the joining materials. At each classification, nanojoining is reviewed and discussed according to materials specialties, low dimensional processing features, energy input mechanisms and potential applications. The preparation of new intermetallic materials by reactive nanoscale multilayer foils based on self-propagating high-temperature synthesis is highlighted. This review will provide insight into nanojoining fundamentals and innovative applications in power electronics packaging, plasmonic devices, nanosoldering for printable electronics, 3D printing and space manufacturing.